"It is amazing how complete is the delusion that beauty is goodness": expectancies associated with tween makeup ownership. (September 2016) - Thyne, Maree; Robertson, Kirsten; Thomas, Tabitha; Ingram, Mikaela
Abstract: Marketing messages socialize individuals into believing that (amongst other practices) consuming cosmetics is the key to beauty and such messages are now being targeted directly to pre‐adolescents. Research shows marketing portrayals of beauty ideals are associated with body disillusionment; however, there is a lack of knowledge on how 'tweens' enculturation of the necessity to consume beauty products influences their personal development and perspectives of others. The present study examines tweens perceptions of girls who own makeup; 111 girls between 6 and 12 years drew and described a child who owned makeup and a child who did not own makeup, resulting in 222 drawings. The drawings and descriptive words were coded inductively using emerging themes and differences between the two drawings were analysed using SPSS and chi‐square analysis. Findings revealed girls who owned makeup were perceived to be more attractive, happy, and popular than girls who did not wear makeup, however, they were also perceived to be "nastier" than girls who did not own makeup. The findings revealed tweens are enculturated into contemporary beauty ideals and hold strong stereotypes regarding owning makeup. Interpreted through the lens of sociocultural theory and the Halo Effect, findings are discussed in terms of how such ideals shape tweens expectations of others and ultimately may shape their own personal behaviour with regards to social interactions, roles and activities engaged in. We argue that the beauty ideal stereotypes associated with tween cosmetic ownership may be in reality, less than ideal.